2006
DOI: 10.2353/ajpath.2006.050404
|View full text |Cite
|
Sign up to set email alerts
|

Lithocholic Acid Feeding Induces Segmental Bile Duct Obstruction and Destructive Cholangitis in Mice

Abstract: We determined the mechanisms of hepatobiliary injury in the lithocholic acid (LCA)-fed mouse, an increasingly used model of cholestatic liver injury. Swiss albino mice received control diet or 1% (w/w) LCA diet (for 1, 2, and 4 days), followed by assessment of liver morphology and ultrastructure, tight junctions, markers of fibrosis and key proteins of hepatobiliary function, and bile flow and composition. As expected LCA feeding led to bile infarcts, which were followed by a destructive cholangitis with activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
144
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 35 publications
8
144
0
1
Order By: Relevance
“…protein and analysis for determination of vascular cell adhesion molecule (VCAM) protein was performed as described. 12 …”
Section: Nm_013693mentioning
confidence: 99%
See 1 more Smart Citation
“…protein and analysis for determination of vascular cell adhesion molecule (VCAM) protein was performed as described. 12 …”
Section: Nm_013693mentioning
confidence: 99%
“…Immunohistochemistry for CD11b, proliferation marker Ki-67, and keratin 19 (K19) were performed as described. 12 mRNA analysis and polymerase chain reaction of several genes was performed as described. 12 Primers used for mRNA analysis of key genes for transporters, metabolic enzymes, inflammation, and fibrosis are summarized in Table 2.…”
Section: Immunohistochemistry For Osteopontinmentioning
confidence: 99%
“…Excess concentrations of bile acids also cause adaptive changes in the liver, such as decreased hepatobiliary transport (Zollner et al, 2003). For example, Fickert et al (2006) have shown that administration of LCA for 4 days in mice can result in hepatocellular necrosis with significant reductions in basolateral bile acid uptake (Ntcp, Oatp1) and increased expression of sinusoidal bile acid efflux transporters (Mrp3). These adaptive changes in the liver represent an attempt to protect cells from the inherent toxicity of accumulating bile acids.…”
mentioning
confidence: 99%
“…Treatment of hepatocytes in vitro with lithocholic acid at a concentration of 1 mM increased mitochondrial membrane permeability and caused cellular lysis (Rolo et al, 2000;Palmeira and Rolo, 2004). Administration of lithocholic acid to experimental animals produced liver and biliary tract injury, including bile duct proliferation, multifocal necrosis with vacuolization, inflammation of the portal area, and atrophy of hepatic lobules (Fickert et al, 2006;Beilke et al, 2008). These pathophysiological changes are indicative of intrahepatic cholestasis and cirrhosis (Palmer and Ruban, 1966;Miyai et al, 1971;Fischer et al, 1974).…”
mentioning
confidence: 99%